2024
DOI: 10.3390/foods13071106
|View full text |Cite
|
Sign up to set email alerts
|

Development of Green and Facile Sample Preparation Method for Determination of Seven Neonicotinoids in Fresh Vegetables, and Dissipation and Risk Assessment of Imidacloprid and Dinotefuran

Osama I. Abdallah,
Rania M. Abd El-Hamid,
Nevein S. Ahmed
et al.

Abstract: A facile procedure for extracting and determining seven neonicotinoids was developed. Water was the only extraction solvent without phase separation and cleanup steps. The method was validated according to European Union standards, and the values obtained were compared with the criteria. The accuracy values were between 99.8% (thiamethoxam) and 106.8% (clothianidin) at the spiking levels of 0.01, 0.1, and 1 mg/kg in the tested matrices. The precision as pooled RSD values was ≤6.1% (intra-day) and ≤6.9% (inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, despite its low toxicity to mammals, there is growing concern about its potential health effects due to its similarity to nicotine and its interaction with nicotinic acetylcholine receptors. Residues of acetamiprid have been detected in diverse media, encompassing natural environments like soil 1 and rivers 2 various food products including vegetables, 3 fruits, 4 honey, 5 and milk, 6 and even human urine. 7,8 Recent studies have also shown adverse effects on non-target organisms 9 and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its low toxicity to mammals, there is growing concern about its potential health effects due to its similarity to nicotine and its interaction with nicotinic acetylcholine receptors. Residues of acetamiprid have been detected in diverse media, encompassing natural environments like soil 1 and rivers 2 various food products including vegetables, 3 fruits, 4 honey, 5 and milk, 6 and even human urine. 7,8 Recent studies have also shown adverse effects on non-target organisms 9 and mammals.…”
Section: Introductionmentioning
confidence: 99%